2017
DOI: 10.1093/jxb/erx356
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for phytol kinase and tocopherol in tolerance to combined light and temperature stress in tomato

Abstract: An essential role is identified for tocopherol in tomato under combined high-light and high-temperature stress. The dual antioxidant and membrane-stabilizing properties of tocopherol may explain its role in combined stress tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 61 publications
3
55
0
Order By: Relevance
“…Values statistically different at P , 0.05 are denoted with different letters. (Spicher et al, 2017). In addition, studies in sunflower (Helianthus annuus) identified responses specific to combined HL1HS involving the upregulation of transcripts associated with energy metabolism, protein synthesis, cell wall activity, and signal transduction components (Hewezi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Values statistically different at P , 0.05 are denoted with different letters. (Spicher et al, 2017). In addition, studies in sunflower (Helianthus annuus) identified responses specific to combined HL1HS involving the upregulation of transcripts associated with energy metabolism, protein synthesis, cell wall activity, and signal transduction components (Hewezi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Phytol is an acyclic diterpene alcohol and a constituent of chlorophyll that is generated from chlorophyll breakdown [36][37][38] . Phytols are essential in the biosynthesis of tocopherols which is a well-known lipid antioxidant and contribute to the protection of photosystem II (PSII) against photodamage under environmental stress 37,39 . On the other hand, a large proportion of phytol and fatty acids is converted into fatty acid phytyl esters in chloroplasts, which are involved in maintaining the integrity of the photosynthetic membrane during abiotic stress and senescence in Arabidopsis thaliana 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Raw data were processed using MassLynx version 4.1 (waters) for automatic peak analysis. Identification and relative quantification were performed as described by Spicher et al (2017).…”
Section: Lipid and Carotenoid Measurementsmentioning
confidence: 99%